A radiopaque electrospun scaffold for engineering fibrous musculoskeletal tissues: Scaffold characterization and in vivo applications. (15th October 2015) - Martin, John T.; Milby, Andrew H.; Ikuta, Kensuke; Poudel, Subash; Pfeifer, Christian G.; Elliott, Dawn M.; Smith, Harvey E.; Mauck, Robert L.
Graphical abstract: Abstract: Tissue engineering strategies have emerged in response to the growing prevalence of chronic musculoskeletal conditions, with many of these regenerative methods currently being evaluated in translational animal models. Engineered replacements for fibrous tissues such as the meniscus, annulus fibrosus, tendons, and ligaments are subjected to challenging physiologic loads, and are difficult to track in vivo using standard techniques. The diagnosis and treatment of musculoskeletal conditions depends heavily on radiographic assessment, and a number of currently available implants utilize radiopaque markers to facilitate in vivo imaging. In this study, we developed a nanofibrous scaffold in which individual fibers included radiopaque nanoparticles. Inclusion of radiopaque particles increased the tensile modulus of the scaffold and imparted radiation attenuation within the range of cortical bone. When scaffolds were seeded with bovine mesenchymal stem cells in vitro, there was no change in cell proliferation and no evidence of promiscuous conversion to an osteogenic phenotype. Scaffolds were implanted ex vivo in a model of a meniscal tear in a bovine joint and in vivo in a model of total disc replacement in the rat coccygeal spine (tail), and were visualized via fluoroscopy and microcomputed tomography. In the disc replacement model, histological analysis at 4 weeks showed that the scaffold was biocompatible and supported the deposition of fibrous tissue in vivo . Nanofibrous scaffolds that include radiopaque nanoparticles provide a biocompatible template with sufficient radiopacity for in vivo visualization in both small and large animal models. This radiopacity may facilitate image-guided implantation and non-invasive long-term evaluation of scaffold location and performance. Statement of Significance: The healing capacity of fibrous musculoskeletal tissues is limited, and injury or degeneration of these tissues compromises the standard of living of millions in the US. Tissue engineering repair strategies for the intervertebral disc, meniscus, tendon and ligament have progressed from in vitro to in vivo evaluation using a variety of animal models, and the clinical application of these technologies is imminent. The composition of most scaffold materials however does not allow for visualization by methods available to clinicians (e.g., radiography), and thus it is not possible to assess their performance in situ . In this work, we describe a radiopaque nanofibrous scaffold that can be visualized radiographically in both small and large animal models and serve as a framework for the development of an engineered fibrous tissue.